DIGITAL MARKETING SKILLS FOR SUSTAINABLE LIVELIHOODS: A CASE STUDY OF ASNAF ENTREPRENEURS - Nazri, Farahana Mohd; Shuib, Fatin Husna; Suki, Amirah Ahmad (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
This study explores the digital marketing skills required to support sustainable livelihoods among Asnaf entrepreneurs in Selangor, Malaysia. As digital platforms increasingly influence small business operations, Asnaf entrepreneurs are encouraged to adopt digital marketing practices to enhance income stability, market reach, and business resilience. However, there remains limited empirical understanding of the specific digital marketing skills needed by this group based on their lived business experiences and challenges. Employing a qualitative case study approach, this study collected data through semi-structured interviews with selected Asnaf entrepreneurs who actively use digital platforms such as social media, messaging applications, and online marketplaces in managing their businesses. The data was analyzed using thematic analysis to identify key skill areas, challenges, and sustainability outcomes. The findings indicate that Asnaf entrepreneurs require essential digital marketing skills, including content creation, ethical online communication, customer engagement, platform management, and basic performance monitoring, to support business continuity and long-term income generation. However, the effective application of these skills is constrained by limited digital literacy, lack of strategic planning capabilities, time constraints, and restricted access to resources. The study concludes that strengthening digital marketing skills is critical for enhancing the sustainable livelihoods of Asnaf entrepreneurs and promoting their long-term economic participation. The findings offer practical insights for entrepreneurship support agencies, policymakers, and training providers in designing targeted digital marketing interventions that align with the needs of Asnaf entrepreneurs and contribute to sustainable development objectives.